JIKEY: preserving the dying arts / Fathiyah Ahmad@Ahmad Jali …[et al.] - Ahmad@Ahmad Jali, Fathiyah; Wan Omar, Wan Noor Faaizah; Subri, Shafilla; Mokhtar, Siti Fairus (Universiti Teknologi MARA, Kedah, 2018)
Jikey is a type of traditional theater dance that was once popular In Kedah and Perlis, especially in the 60s. Unfortunately, it went off the radar for quite sometimes that most young generati6n nowadays are not aware of the existence of this unique theatre dance. Thus, this Is an effort to give awareness and Information and wet as preserve this cultural entity that our next generation knows and appreciates it. This concept idea is meant to re-introduce the arts into the mainstream arts and made it known to the people. The Jikey performance has a strong influence from other Malay performing Arts like Mak Yong, Hadrah, Bangsawan arRi Mek Mulung. The main elements of Jikey are improvised dialbgue, muse and dance, and local legends formed the main repertoire with considerable emphasis placed on slapstick comedy.The Jikey music consists of both instrumental and singing. The main characters are comedians, king and warriors. A complete theatrical orchestra for likey includes rebana (with no jingles) in large, medium and small sixes; one tambourine; one hanging, knobbed gong, fare or more pain of cerek, one pair of kesi, an oboe (serunai for Malay or pi for Thai). However, typical ensembles consist only ofd violin, 3 rebana and 2 cerek or bamboo stampers.